2010
DOI: 10.24908/ss.v7i3/4.4156
|View full text |Cite
|
Sign up to set email alerts
|

The Social impact of Surveillance in Three UK Schools: Angels, Devils and Teen Mums

Abstract: Drawing upon the preliminary findings of a broader ESRC-funded project on the ‘surveilled’, this paper examines the social impact of ‘new surveillance’ technologies on the lives of school children living in a Northern City. We conducted fifteen one-hour ‘focus groups’ with eighty-five 13 to 16 year-old children in three schools. The pupils were asked a range of questions designed to document their awareness, experience and response to ‘surveillance’ as ‘school children’, but also as ‘regular citizens’ going ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 15 publications
(10 reference statements)
0
25
0
Order By: Relevance
“…Interestingly, the only form of victimization associated with school security measures was one that appears least likely to be detectable by school security measures. This sort of adaptive behavior whereby students misbehave in ways that are undetectable by school security measures has been found in prior qualitative research examining behaviors around school security cameras (McCahill and Finn 2010; Weiss 2008). This pattern may indicate that school security measures can limit increases in clearer, more objective forms of victimization, but not more subtle, interpretable forms.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, the only form of victimization associated with school security measures was one that appears least likely to be detectable by school security measures. This sort of adaptive behavior whereby students misbehave in ways that are undetectable by school security measures has been found in prior qualitative research examining behaviors around school security cameras (McCahill and Finn 2010; Weiss 2008). This pattern may indicate that school security measures can limit increases in clearer, more objective forms of victimization, but not more subtle, interpretable forms.…”
Section: Discussionmentioning
confidence: 61%
“…Other research has argued that those who are perceived to be in need of surveillance are positioned as suspects (Monahan & Torres, 2010). McCahill and Finn (2010) suggested that the females in their study were more acutely aware of being under surveillance because women's bodies already tend to be more scrutinised than men's. As racial minorities are already frequently positioned as threatening or suspects, and are already more scrutinised than whites, it makes sense to assume that school surveillance is likely to impact more harshly on racial minorities than their white counterparts, and these discourses are likely to build on longstanding notions of perceived essentialised links between minority ethnic bodies and criminality and threat (Oztas, 2011).…”
Section: Linking School Surveillance Counter-terrorism and Racementioning
confidence: 95%
“…A small amount of work has been done in the US (Monahan & Torres, 2010;Simmons, 2010), and I have been able to find nothing in the UK. A recent project on the 'surveilled' (McCahill & Finn, 2010) examined the social impact of new surveillance technologies on the lives of school children living in a Northern English city, including looking at 13 to 16 year-old children in three schools. It found that children's experiences differed across social class and gender, but did not examine the implications for race.…”
Section: Linking School Surveillance Counter-terrorism and Racementioning
confidence: 99%
“…Examples include, Fotel and Thomsen (2004) who examine child mobility in surveillance society -arguing that the increasing levels of surveillance are changing what it means to be a child; Marx and Steeves (2010) who argue that CST have the dual purpose of keeping children safe and stopping them behaving inappropriately; McCahill and Finn's (2010) exploration of child surveillance in terms of gender and class; and Rooney's research (2010) discussing the impact on children's identity development in a culture that increasingly defines itself as inherently unsafe. With few exceptions (e.g.…”
Section: Trax Gps Tracker Online Advertisingmentioning
confidence: 99%